Overview of a New Reconstruction Method to Map the Ionosphere at the Brazilian Region - Prol, Fabricio dos Santos [UNESP]; Inst Navigat (Inst Navigation, 2018)
Three-dimensional ionospheric reconstruction at the Brazilian area has been a continuous challenge due to the high ionospheric variability and lack of data in the region. Many efforts have been conducted to overcome these problems with the main idea of efficiently mapping the ionosphere for applications concerning geodetic positioning, telecommunication and space weather. In this regard, tomographic algorithms have been continuously investigated by the authors and, in this paper, we present an overview of a method that significantly improved the results for the regional estimation. The proposed method is based on a new climatological model developed with ionosonde and Radio-Occultation (RO) measurements, which revealed new spatial and temporal features of the of topside scale height and its gradient. The climatological model was also developed to obtain an initial guess of the ionosphere, i.e. a background. Then, a new version of the Multiplicative Algebraic Reconstruction Technique (MART) was used to iteratively update the background by adding information retrieved from ground-based measurements of Total Electron Content (TEC). As a result, three-dimensional representations were generated, applied and assessed in the single-frequency Precise Point Positioning (PPP). Additional results are presented about the performance of the method to describe the ionospheric topside and bottomside and for mapping plasma bubbles.